Apical leakage of root canal system obturation materials - Mitić Aleksandar; Mitić Nadica; Tošić Goran (Serbian Medical Society - Dental Section, Belgrade, 2005)
Hermetical obturation on dentine-cement junction is one of the conditions for success in endodontic treatment. The aim of this paper was to evaluate apical obturation of three different root canal obturation materials. Methods consisted of in vitro semiquantitatively measured penetration of colored solutions. Total number of 55 single-canal teeth was used and obturation test materials were AH-plus, Ketac-Endo and Endomethasone. Linear color penetration was evaluated following illumination of teeth in 2% sol. Metylsalicilate. Results obtained have shown better adhesion between sealer and root canal walls, i.e. better apical obturation when AH-plus (0.25mm) and Ketac-Endo (0.52mm) were used and highest rate of apical leakage when Endomethasone was used (2.35mm). None of the tested obturation materials have sealed apical portion completely.